The use of continuous system identification for evaluation of concrete e-modulus evolution : laboratory and field applications - Aguilar, Rafael (2012)
For many engineering areas, the knowledge of the variation of the mechanical properties of hardening materials (such as concrete) since early ages, and throughout service life is of interest not only for academic purposes but also for practical reasons. In case of the precast or in-situ construction industry, tracking the evolution of concrete mechanical properties since the instant of casting is of high importance due to the fact that the volume of the production and the cost of the final product are directly linked to the optimization of the process of removing the formwork (and/or applying pre-stress) as early as possible. The paper presents the application of a recently devised method to track the hardening process of concrete, which is based in the correlation of the changes in the dynamic response of structural systems (that contain the tested material), with the stiffness evolution of the tested material. The paper focuses in the presentation of the operational modal identification tests that were carried out in laboratory and in-situ, as well as the presentation of a new automatic identification algorithm based in the SSI-Data method which was used to process the large amount of recorded data. The results of the tests show the feasibility of the application of Operational Modal Analysis (OMA) techniques for accurately assessing the dynamic response of the tested specimens even in environments with high noise levels. It is also shown that accurate approximations of the instantaneous E-modulus of the concrete can be obtained with the application of the proposed methodology.